Improved flexible laser endoscope system for photodynamic tumor therapy - 正宗, 賢; 三木, 康平; Yan, Hu (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
Photodynamic therapy (PDT), which is already applied in clinical case, selectively destroys tumor cells by the combination of photosensitizer and corresponding-wavelength laser. Our previous flexible laser endoscope properly achieved a main challenge caused by present endoscope and laser fiber technologies, which could not control the laser irradiation target during therapy, and this would hurt surrounding healthy tissue or blood vessel, causing bad complications. However this system exists its own shortcomings: its view angle less than 30 degree, not high image resolution, large laser focusing spot, and unstable XY stage placement rendering a litter large positioning errors. In this paper, we improve the system respecting aforementioned drawbacks. Experimental results prove the effectivity of this improved flexible laser endoscope system: the view angle larger than 70 degree, image resolution 5 times of standard laparoscopy, laser focusing spot almost half of previous, and horizontal stage placement giving out better positioning accuracy.